Evaluasi Karakter Agronomi Mutan Putatif Bawang Putih Generasi Mv2 Hasil Iradiasi Gamma Pada Dataran Tinggi - Utin Winarni; Dini Dinarty; Fahrudin Arfianto (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
Garlic has a narrow diversity because it is propagated vegetatively. Mutation breeding can be used to produce diversity in a short time but has the disadvantage of randomness and instability of genetic traits that appear in the next generation. The purpose of this study was to evaluate the agronomic characters and to obtain the MV3 generation garlic putative mutants which have better adaptability to highland areas with better performance. The planting material used was MV2 generation garlic in the form of bulbil and cloves from single technique gamma ray irradiation (Acute Irradition). The garlic genotypes used were Lumbu Kuning, Ciwidey and Tawangmangu Baru. Clove planting material at LD50 and doses above LD50, bulbil LD20. The dosage levels used for cloves were: Tawangmangu Baru 8 Gy (LD50) and wild type (control), Lumbu Kuning 10 Gy and wild type (control), Ciwidey 6 Gy (LD50), 8 Gy (dose above LD50) and wild type ( control). Dosage levels for bulbil: Ciwidey 1.75 Gy and Tawangmangu Baru 0.5 Gy. The results showed that the CWS 8 Gy and LKS 10 Gy mutants had higher number of cloves and tuber weight than the control. Varigata was present only in the CWS 8 Gy mutant. Analysis of the main components of the quantitative and qualitative properties of garlic was reduced to 8 main components.